Breakdown strength analysis of XLPE insulation types: A comparative study for multi-layer structure and voltage rise rate - Camalov, Mehti; Orucov, Allahverdi; Hashimov, Arif; Arikan, Oktay; Akin, Firat (ELSEVIER SCIENCE SA, 2023)
Multi-layered structures are commonly used in high voltage applications to improve the electrical, mechanical, and thermal stability of insulation systems. This study investigates the breakdown strength of two commonly used cross-linked polyethylene (XLPE) types by conducting detailed experiments considering the effects of multi-layered structures, material thicknesses, and voltage rise rates. Although there are existing studies on the impact of thickness and voltage rise rate, there is a paucity of research specifically focusing on these factors within the framework of multi-layered structures. Experimental results showed that the breakdown strength of both samples exhibited greater values at the higher voltage rise rate. When the breakdown strengths were examined according to the layer structure, it was seen that the multi-layer insulation structures had higher breakdown strengths. Specifically, the maximum increases were 17.96% and 23.80% for peroxide-added and silane-added XLPE samples, respectively. Moreover, it was revealed that silane-crosslinked samples had higher breakdown strengths in all cases. Finally, the structures of the test samples were examined by scanning-electron microscope (SEM) analysis and the impacts of the findings were evaluated through the simulations in COMSOL Multiphysics (R). Simulation results showed that rough and inhomogeneous material structure dramatically increased the electric field intensity acting on the multi-layer insulations.
Keywords: Breakdown strength; Polymer insulation; Multi-layered insulation; XLPE; Voltage rise rate; Scanning-electron microscope; Finite element analysis; COMSOL Multiphysics & REG; software; CROSS-LINKED POLYETHYLENE; SPACE-CHARGE; POLYMERS; Engineering